Evaluation of spatial and temporal accuracy of GPCC and CRU datasets against observational data - Hadi Razzaq Abed; jafar Masoompour Samakosh; Morteza Miri; Tayeb Raziei (مطالعات جغرافیایی مناطق خشک)
Aim: This study investigates the accuracy and reliability of GPCC and CRU data for conducting various hydroclimatic studies in Iraq. Material & Method: The data used include monthly precipitation data from the GPCC database with a spatial resolution of 0.5° and 0.25° geographical latitude and longitude, and monthly precipitation, minimum and maximum temperature data from the CRU database with a spatial resolution of 0.5° geographical latitude and longitude over the period 1990–2020. R, R2, EF, BIAS, RMSE, and Slope statistics were used to evaluate the accuracy of the data. Finding: According to the validation results, GPCC and CRU exhibit satisfactory accuracy in estimating precipitation minimum and maximum temperatures in Iraq. GPCC shows a high correlation coefficient (0.71-0.87) in estimating precipitation in Iraq's eastern and northern provinces. The Slope statistic ranges between 0.80 and 1.2, and the NRMSE is less than 3 in most stations. CRU demonstrates a high correlation coefficient (R≈0.81), EF>0.5, NRMSE<2, and Bias between -2 and 6 mm in estimating precipitation in the eastern and northern parts of the country. Furthermore, CRU exhibits high accuracy in estimating minimum and maximum temperature in Iraq; as such, the CRU data and observed data at stations exhibit strong agreement, with R>0.96, R2>0.95, EF>0.95, Slope>0.95, and NRMSE around less than 1.5 in most regions. Conclusion: Based on the validation results, GPCC and CRU have suitable accuracy in estimating rainfall minimum and maximum temperatures in Iraq. Therefore, GPCC and CRU data can be introduced as reliable sources for analyzing precipitation and temperature patterns and in areas lacking data in Iraq. Innovation: Both data sources provide the possibility of analyzing precipitation and temperature patterns, as well as important decision-making steps related to water management and adaptation to climate change.